Sense of Coherence and Tobacco Use Myths among Adolescents as Predictors of At-Risk Youth Cigarette Use - El-Shahawy, Omar (Subst Use Misuse, 2014)
We examined the association between a general construct of wellness beliefs, sense of coherence, and a specific measure of tobacco-related beliefs, tobacco use myths, as predictors of two smoking -related outcome measures - next year smoking expectation and last 30-day smoking. Self-report questionnaires were administered to 710 adolescents attending California continuation high schools at baseline and at one-year follow-up between 2006 and 2008. Cross-sectionally, predictor and outcome measures were correlated. However, in longitudinal analyses, only tobacco use myths predicted change in outcome measures. We speculate that future smoking interventions among adolescents would achieve relatively efficacious outcomes by targeting specific health beliefs instead of global health beliefs. The study’s limitations are noted. Funding: National Institute on Drug Abuse and Tobacco Related Disease Research Program.